Characterization of complexation of poly (N-isopropylacrylamide-co-2-(dimethylamino) ethyl methacrylate) thermoresponsive cationic nanogels with salmon sperm DNA - Jim Moselhy (Dove Medical Press, 2009)
Jim Moselhy1, Tasnim Vira1, Fei-Fei Liu2, Xiao Yu Wu11Department of Pharmaceutical Sciences, Leslie Dan Faculty of Pharmacy, University of Toronto, Toronto, ON, Canada; 2Ontario Cancer Institute, Toronto, ON, CanadaAbstract: Thermoresponsive cationic nanogel (TCNG) networks based on N-isopropylacrylamide (NIPAM), 2-(dimethylamino)ethyl methacrylate (DMAEMA), and quaternary alkyl ammonium halide salts of DMAEMA (DMAEMAQ) were synthesized by dispersion polymerization technique. The thermoresponsive properties of TCNGs and TCNG-salmon sperm DNA (sasDNA) polyplexes were characterized in aqueous media of various pH and ionic strength. P[NIPAM] and P[NIPAM/DMAEMA] TCNGs exhibited sharp volume phase transition (VPT) in water at critical temperatures (Tc) of 32 °C and 36 °C, respectively. Quaternized P[NIPAM/DMAEMAQ] TCNGs did not undergo sharp VPT up to 50 °C. The VPT of uncomplexed TCNGs were sensitive to the ionic composition and ionic strength of salts in solution, but were insensitive to pH in the range 5.0 to 7.4. The VPT of P[NIPAM/DMAEMAQ]/sasDNA diminished in magnitude with increasing Wp/Wd suggesting greater compaction of the polyplexes. The distinct phase-transition properties of P[NIPAM/DMAEMA]/sasDNA and P[NIPAM/DMAEMAQ]/sasDNA polyplexes were attributed to the condensing capability of polycations and to differences in the spatial distribution of structural charges in quaternized and nonquaternized networks. The findings demonstrate that stable TCNGs can be prepared with controllable responsive properties determined by the nature of the cationic charge incorporated and may have potential as vehicles for DNA delivery.Keywords: poly(N-isopropyl acryamide), poly(2-dimethylamino)ethyl methacrylate, polyplex, thermoresponsive cationic nanogels